Expanding the Phenotypic and Genotypic Spectrum of ARFGEF1-Related Neurodevelopmental Disorder - Xu, Lu; Zhou, Youfeng; Ren, Xiaoyan; Xu, Chenlu; Ren, Rongna; Yan, Xuke; Li, Xuelian; Yang, Huimin; Xu, Xuebin; Guo, Xiaotong; Sheng, Guoxia; Hua, Yi; et al. (Frontiers in Molecular Neuroscience, 2022)
Background Mono-allelic loss-of-function variants in ARFGEF1 have been recently reported to cause developmental delay, intellectual disability, and epilepsy with variable expressivity. However, the strength of gene–disease association need more evidence, given clinical heterogeneity and low- penetrance variants of ARFGEF1-related neurodevelopmental disorder. Methods Through a search of our local data lake with information from whole-exome sequencing (WES) >60,000 probands, we queried for rare variants in the ARFGEF1 gene. Results we identified five unrelated pediatric patients with novel heterozygous (likely) pathogenic ARFGEF1 variants, including one missense change (c.3539T>G), two canonical splice site variants (c. 917-1G>T, c.2850+2T>A) and two frameshift variants (c.2923_c.2924delCT, c.4951delG) that likely introduce a truncation. The (likely) pathogenic variants presented here will be greatly beneficial to patients undergoing genetic testing in the future by providing an expanded reference list of disease- causing variants. Further, based on own data repository, we proved that the vast majority of rare missense mutations and some putative protein-truncating variants of ARFGEF1 were not disease- causing, implying interpretation of variation needs more cautious. Conclusion we expanded the genotypic spectrum of ARFGEF1-related neurodevelopmental disorder, including five novel heterozygous (likely) pathogenic variants and nine non-pathogenic protein- truncating variants.